2007
DOI: 10.1159/000099104
|View full text |Cite
|
Sign up to set email alerts
|

Valvular Heart Disease by Transthoracic Echocardiography Is Associated with Focal Brain Injury and Central Neuropsychiatric Systemic Lupus Erythematosus

Abstract: Background: Previous studies using transesophageal echocardiography (TEE) report an association of valvular heart disease (VHD) with cerebral infarcts and central neuropsychiatric systemic lupus erythematosus (NPSLE). However, TEE cannot be routinely used. Aim: To determine if VHD detected by transthoracic echocardiography (TTE) is associated with focal brain injury on magnetic resonance imaging (MRI) and secondarily with central NPSLE. Methods: Sixty-nine patients with systemic lupus erythematosus underwent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…In another TTE study, any valve abnormality detected in 44% of 71 patients was associated with past stroke/TIA (30). In 3 retrospective studies from our institution (2 using TEE), valve vegetations were associated with past stroke/TIA, non-focal NPSLE, and brain lesions on MRI (3133). In a prospective not-controlled TTE study, Libman-Sacks vegetations detected in 11% of 342 SLE patients were associated with a higher incidence of stroke/TIA (14.8% in those with versus 3% in those without vegetations) during a 4-year follow-up (34).…”
Section: Discussionmentioning
confidence: 99%
“…In another TTE study, any valve abnormality detected in 44% of 71 patients was associated with past stroke/TIA (30). In 3 retrospective studies from our institution (2 using TEE), valve vegetations were associated with past stroke/TIA, non-focal NPSLE, and brain lesions on MRI (3133). In a prospective not-controlled TTE study, Libman-Sacks vegetations detected in 11% of 342 SLE patients were associated with a higher incidence of stroke/TIA (14.8% in those with versus 3% in those without vegetations) during a 4-year follow-up (34).…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search identified 234 publications, of which 23 unique studies were included in the review 13,21,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] ( Figure 1). Studies were identified with the use of Embase (nϭ115), MEDLINE (nϭ97), Cochrane Library (nϭ0), and hand search (nϭ22) from August 1987 to December 2010.…”
Section: Literature Flow Chartmentioning
confidence: 99%
“…A prospective study of 70 SLE patients by Cervera et al [59] suggests a more benign prognosis, with only approximately 4% of patients developing clinically significant valvular disease and only approximately 2% requiring surgical intervention. Studies by Roldan et al demonstrate associations between valvular heart disease in SLE and both focal brain injury and nonfocal neuropsychiatric disease [67,71,72]. Similarly, other studies have demonstrated associations between valvular heart disease in SLE and central nervous system disease.…”
Section: Clinical Featuresmentioning
confidence: 88%